Anaerobic alactic energy assessment in middle distance swimming - Sousa, A.; Figueiredo, P.; Zamparo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (European Journal of Applied Physiology, 2013)
To estimate the anaerobic alactic contribution in a 200 m middle distance swimming trial by means of two different methods based: (1) on the fast component of the VO2 off-kinetics (Anarecovery) and (2) on the kinetics of maximal phosphocreatine splitting in the contracting muscle (Anapcr). Ten elite male swimmers performed a 200 m front crawl trial at maximal velocity during which VO2 was directly measured using a telemetric portable gas analyser; during the recovery period VO2 data were collected until baseline values were reached. No significant differences between the two methods were observed; mean ± SD values were 31.7 ± 2.5 and 32.6 ± 2.8 kJ, for Anapcr and Anarecovery, respectively. Despite the existence of some caveats regarding both methods for estimation of the anaerobic alactic contribution, data reported in this study indicate that both yield similar results and both allow to estimate this contribution in supra-maximal swimming trials. This has important implications on swimming energetics, since the non-inclusion of the anaerobic alactic contribution to total metabolic energy expenditure leads to an underestimation of the energy cost at supra-maximal speeds.